Oblique Corrections in the MSSM at One-Loop—Part I: Scalars - Yao Yu; Sibo Zheng (Advances in High Energy Physics)
This paper is devoted to reconsider the one-loop oblique corrections arising from the scalar superpartners in the MSSM, that is, the squarks, the sleptons, and the scalars in Higgs sector. We explicitly present the complete one-loop forms of self-energy corrections to the gauge bosons of SM electroweak gauge groups, as well as their descendants the